THE USE OF ENGAGE, STUDY, ACTIVATE (ESA) METHOD TO ENHANCE THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Sujariati, Sujariati; Sastrawati , Ika (Publikasi dan UKI Press UKI Toraja., 2023)
This research aimed at enriching the students’ writing ability particularly content and organization in writing descriptive text by using Engage, Study, Activate (ESA) Method. A pre-experimental design was employed with one group pre-test and post-test design. The sample was only one class consisting of 30 students that was selected by using purposive sampling technique. The data were obtained through writing test. Findings showed that the students’ mean score in pre-test was 4.23 and it was improved to be 7.2 in post-test. Therefore, the statistical computation described that Engage, Study, activate (ESA) Method was effective in improving the students’ writing ability in descriptive text. It is supported by the value of t-test that is bigger than the value of t-table (18.5>2.045). Therefore, the Alternative Hypothesis was accepted and the Null hypothesis was rejected. Designing the learning purpose appropriately which considers students’ needs and language level may ease teachers to use the Engage, Study, activate (ESA) Method in improving students’ writing descriptive text. The teachers may try to take advantage of Engage, Study, activate (ESA) Method to be utilized in their class room activities to conduct an effective and interesting learning atmosphere in the classroom.